Prediction of Behavioral T/C Levels in Cochlear Implant Patients Based Upon Analysis of Electrode Impedances - Zarowski, A.; Molisz, A.; Cardinael, E.; Vermeiren, A.; Theunen, T.; De Coninck, L.; Theuwis, L.; Siebert, J.; Offeciers, F.E. (Journal of the American Academy of Audiology, 2020)
Background Fitting cochlear implants in babies and noncooperative patients is cumbersome and time consuming. Therefore, objective parameters have been sought in order to predict the subjective threshold (T) and maximum comfort (C) levels. Measurements of the electrically evoked compound action potentials (ECAPs) have been widely used for this purpose, yet the correlation between these objective measures and the subjective T/C levels is weak to moderate.Purpose This article aims (1) to evaluate correlations between the subjective parameters of the fitting maps such as thresholds (T level) and maximum comfort levels (C level), the impedance of the electrode contacts, and the ECAP thresholds, and (2) to compare the value of the electrode impedances and the ECAP measures for prediction of the T/C levels.Research Design Case review study in a quaternary otologic referral center.Study Sample Ninety-eight consecutive CI patients were enrolled. The average age of the patients was 49 years. All patients were users of the Nucleus 24RECA (Freedom, Contour Advance-of-Stylet electrode) cochlear implant.Data Collection and Analysis Data on impedance of the electrode contacts and the behavioral T/C levels at the first fitting session (2–5 weeks after surgery) and at the 5th fitting session (4–6 months after surgery) have been retrospectively collected in 98 consecutive CI patients. Additionally, the intraoperative impedance values and the ECAP thresholds (tNRT) have been recorded.Results Impedances of electrode contacts show significant strong negative correlations with the stabilized T/C levels at 4 to 6 months after implantation and are an important predictor for the behavioral T/C levels. They can explain R2 = 28 to 41% of the variability of the behavioral T/C levels. In multiple regression analysis electrode contact impedances can explain twice as much of the variability of the stabilized T/C levels than the tNRT values. The electrode impedances together with the tNRT values are able to explain R2 = 37 to 40% of the global variability of the T/C levels while the tNRT thresholds solely are able to explain only R2 = 5 to 14% of the T/C levels variability.Conclusion Impedances of electrode contacts correlate strongly with the stabilized behavioral T/C levels and may be used as an objective measure for fitting of cochlear implants.
Keywords: cochlear implants; impedance; ECAP; tNRT; T/C levels; correlation